A study on customers level of satisfaction on services provided by Multimedia College (Sabah) / Marida Sungkin - Sungkin, Marida (2006)
A study was conducted on customers' level of satisfaction on services provided by Multimedia College (Sabah). Objectives of the study are to know the level of satisfaction among TM employees that based on demographic, to determine which SERVQUAL dimension that needs to be improved, and to identify customers' expectation in future for MMC. The study comprises of five chapters. The first chapter contains introduction of the study. Literature review in chapter two, where secondary data obtained, that are relevant and supporting the study, are consists of reference books, website, and dictionary as well. Research methodology and design in chapter three is the key elements in the study. A theoretical framework is produced which indicates customer satisfaction as dependent variable, and, reliability, responsiveness, assurance, empathy and tangible dimension as independent variables of the study. The collection of primary data is gathered from survey that conducted through questionnaires and personal interview. The study complies of non-probability and convenience sampling is chosen as the sampling technique. Sample size is 278 out of 1126 of its population. Sampling frame is employees of Telekom Malaysia who work in the area of Kota Kinabalu. By using Statistical Package for Social Science (SPSS), data that collected from 278 respondents are analyzed and interpreted in the forms of frequency distribution and cross tabulation, as in chapter four of this study. The results are presented in tabular and chart forms. Finally, conclusion and recommendations are forwarded primarily for academic purposes and further study and evaluation.